Asthma: Achievements and Questions in Front: Asthma: achievements and questions in front - Salamzadeh, Jamshid (Iranian Journal of Pharmaceutical Sciences, 2005)
Asthma, which is mainly distinguished by airway inflammation and bronchial hyper-responsiveness, is known as one of the most common chronic diseases worldwide. It also is the most frequent chronic respiratory disorder amongst all age groups. On one side of the asthma story, there are massive investment of time, effort and money, a large number of pharmaceutical and academic research studies, health service modifications and revised guidelines. On the other side, there are unacceptably high, but mostly preventable, morbidity and mortality rates, socio-economic burdens and psychological problems due to asthma. A considerable proportion of doctor’s workload, hospital resources, health utilization costs, days off from school and work are caused by asthma. Our knowledge about this disorder and its complications is still on demand. There are significant questions regarding asthma and its pathophysiology which should be answered. National, regional and local initiatives are needed to be established to help health systems to overcome socio-economic burdens due to this disease. These could only be done if a clear picture of this respiratory disorder and its management achievements are available. This review article is an approach to present an image about asthma and its management based on the current understandings of the nature of this disorder.